Who Went South? The German Ethnic Niche in the Northern and Southern Hemispheres. Issue 3 (25th July 2017) - Kamphoefner, Walter D.
Abstract : This article examines the demographic and occupational selectivity of German immigration to South America (primarily Argentina and Brazil) and Australia, compared to Germans bound for the United States, and the geographic and occupational niches they occupied at various destinations. It draws upon both individual-level and aggregate data from censuses and migration records on three continents to examine occupational profiles, urbanization rates, sex ratios, age structure, and age heaping as a rough measure of "quality, " among German immigrants to these destinations, concluding that immigration to the United States tended to be the least selective.